Implementation of Integrative Thematic Learning to Teach Aqidah Akhlak (Moral Education): A Case in an Islamic Primary School in Indonesia - Baharshah , Awaludin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This study aimed at (1) analyzing the integrative thematic learning planning in the subject of Aqidah Akhlak subject, (2) analyzing the implementation of integrative thematic learning in the Aqidah Akhlak subject, (3) analyzing the evaluation of integrative thematic learning in the subject of Aqidah Akhlak, and (4) analyzing the supporting and inhibiting factors of integrative thematic learning in the Aqidah Akhlak subject. In this study, the author used a qualitative approach. This study obtained descriptive data that describes planning, implementation, evaluation, and the supporting and inhibiting factors of integrative thematic learning in the subject of Aqidah Akhlak with a research location at MI Istiqomah Sambas Purbalingga, Indonesia. In contrast, the data was obtained through interviews, observation, and documentation and then processed into information. The results of this study show that the implementation of integrative thematic learning in the subject of Aqidah Akhlak was conducted through three stages. First, initial activities, including greeting, asking for news, and attendance of students. Second, core activities include four activities: observing, asking questions, concluding, and discussing results. Third, the final activity includes giving homework and ending with closing greetings.